Body mass index, disease duration and tumor necrosis factor inhibitor history predict reduced ustekinumab response in Chinese psoriasis patients: A real-world study - Xue Xu; Guifang Qin; Zudong Meng; Dan Pei (Wolters Kluwer Medknow Publications, 2021)
Background: Ustekinumab, as a monoclonal antibody against interleukin (IL)-12 and IL-23, gets approved in China since 2019, therefore fewstudies report the application of ustekinumab in treating Chinese psoriasis patients in the real clinical settings until now. Aims: Thus, this study aimed to evaluate treatment efficacy, treatment response-related factors, and safety of ustekinumab in treating Chinese psoriasis patients. Materials and Methods: Totally, 72 moderate-to-severe plaque psoriasis patients who underwent ustekinumab treatment were analyzed. Their clinical data were recorded. Furthermore, improvement of psoriasis area severity index (PASI) score more than 75% (PASI75) and improvement of PASI score more than 90% (PASI90) at week 12 and week 24 were retrieved. Besides, the adverse events were reviewed. Results: There were 72.2% and 37.5% psoriasis patients who achieved PASI75 response and PASI90 response at week 12. Meanwhile, 86.7% and 46.7% psoriasis patients realized PASI75 response and PASI90 response at week 24. Besides, multivariant logistic regression analyses revealed that body mass index (BMI), disease duration, and history of tumor necrosis factor (TNF) inhibitors could independently predict reduced ustekinumab response in psoriasis patients. Additionally, the most common adverse events of ustekinumab treatment in psoriasis patients were infection (12.5%) and nasopharyngitis (9.7%), followed by headache (4.2%), cough (4.2%), abnormal hepatic function (4.2%), injection site reactions (2.8%), and eosinophilia (1.4%), which were all mild and manageable. Conclusions: Ustekinumab is an effective and safe immunotherapy drug for treating Chinese psoriasis patients. Furthermore, BMI, disease duration, and history of TNF inhibitors are predictors of poor ustekinumab response.